Two Case Reports of Familial Chylomicronemia Syndrome - Yan-Hui Chen; Zhong-Ling Ke; Yan-Xia Wang; Yong Wang; Yong-Zhi Zheng (Hindawi Limited, 2012)
Familial chylomicronemia is a rare autosomal recessive disorder which is also called Hyperlipoproteinemia type I. Here we report two cases with this rare disorder that were admitted to our hospital in recent years.